Effect of bar jump height on kinetics and kinematics of take-off in agility dogs - Leena Inkilä; Anna Boström; Pedro Valadão; Janne Avela; Simon Walker; Johanna Mäkitaipale; Anna Bergh; Heli K. Hyytiäinen (PLoS ONE, 2025)
Sport-related injuries have been reported to occur in around one-third of agility dogs. Higher bar height in competitions has been shown to increase odds of an injury. This study evaluated the effect of bar height on the kinetics and kinematics at take-off to a bar jump. Forces from fore- and hindlimb pairs were measured with force plates. A three-dimensional motion capture system was used to measure sagittal joint kinematics of the shoulder, elbow, carpus, hip, stifle, and tarsal joints, as well as limb coordination, trunk horizontal velocity, take-off distance, and take-off angle. Data were collected for 17 Border Collies at three different bar heights: 80%, 100%, and 120% of wither height. A linear mixed model was used for statistical analysis. At higher bar height, decelerative impulses were greater and accelerative impulses decreased along with greater vertical impulses from forelimb and hindlimb pairs (p<0.001). Post-hoc analyses revealed differences between all three bar heights (p<0.01), except for forelimb decelerative impulse, which did not differ between 80% and 100% heights. Sagittal range of motion was greater, through increased peak flexion or extension, at 120% bar height than at lower bar heights (p<0.05) in almost all measured limb joints. The only exceptions were leading forelimb shoulder and elbow joints and leading hindlimb hip joint. With increasing bar height, the horizontal velocity of trunk decreased (p<0.001), and take-off angle became steeper (p<0.001), with all bar heights differing from each other (p<0.01). Temporal synchronicity between trailing and leading limbs increased and craniocaudal distance decreased in forelimbs (p<0.05) and hindlimbs (p<0.01) as bar height increased. Increased vertical and decelerative impulses, as well as the greater peak flexion and extension angles of joints, may indicate greater load on the tissues at higher bar heights, which could explain the increased odds of injury at higher bar heights in agility dogs.